Investigation of heuweltjie structure and soil chemistry in the Buffels River valley and implications for transfer of salts to groundwater - Vermooten, Marli (Stellenbosch : Stellenbosch University, 2019)
Thesis (MSc)--Stellenbosch University, 2019.